Active agents loaded extracellular matrix mimetic electrospun membranes for wound healing applications - Sumama Nuthana Kalva (17302906) (2021)
Achieving the healing of chronic diabetic ulcers, burn wounds and large traumatic wounds is a major clinical challenge. A variety of approaches have been undertaken to generate skin substitutes, wound healing patches or dressings with adequate barrier properties, stability, degradation, exudate uptake capacity, antimicrobial properties, vascularization potential and wound-healing capacity. Recent approaches to support chronic wound healing focus on the development of a natural extracellular matrix (ECM) mimetic microenvironment in the wound bed. Submicron fiber-based membranes have been shown to successfully mimic many features of the ECM such as its architecture, mechanical properties, composition, and function. Electrospinning is one of the most successful methods for producing porous submicron fiber based wound coverage matrices for promoting wound healing and achieving tissue regeneration. The ECM mimetic properties of the membranes have also been improved with the use of recently developed methods such as coaxial electrospinning with other polymers. Various active components such as therapeutic agents, nanoparticles and biomolecules can be incorporated in electrospun fibers to improve ECM mimetic features and provide additional advantages like antibacterial and angiogenic properties. This article comprehensively overviews the applications of ECM mimetic electrospun membranes as structural and functional components in wound healing and the potential challenges imposed by them in a clinical point of view. Other Information Published in: Journal of Drug Delivery Science and Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jddst.2021.102500